Trust, religiosity commitment, and nisbah perception in shaping customer loyalty - Rosula, Vera; Sudiro, Achmad; Mugiono; Rohman, Fatchur (Asian Economic and Financial Review, 2024)
This study investigates the factors influencing customer loyalty in Sharia banking, with a focus on trust, religiosity commitment, and the perception of nisbah (profit-sharing ratio). By exploring the interplay between these variables, the research aims to provide insights into the mechanisms driving customer loyalty within Islamic banking institutions. Utilizing partial least squares structural equation modeling (PLS-SEM), data was collected from 212 priority customers of Bank Syariah Indonesia (BSI) in the Jabodetabek region. The study examines the direct and indirect effects of trust on loyalty, the mediating role of religiosity commitment, and the moderating influence of nisbah perception. The findings underscore the significance of trust in fostering customer loyalty in Sharia banking. Trust directly influences both religiosity commitment and loyalty, with religiosity commitment serving as a partial mediator between trust and loyalty. Furthermore, nisbah perception moderates the relationship between religiosity commitment and loyalty, indicating its role in shaping customer loyalty within Sharia banks. The study highlights the importance of transparency, adherence to Sharia principles, and the effective communication of transaction costs and risks in building trust and maintaining customer loyalty. Policy recommendations include prioritizing service improvements, reinforcing halal fund management practices, and enhancing employee competence to better serve priority customers. However, limitations such as restricted interaction with respondents and sample size constraints are possibilities for future research to enhance the robustness of the findings.